MARRIAGE NULLITY IN CANON LAW - Dan, Dotiu (Anales Universitatis Apulensis Series Jurisprudentia; No 15 (2012): ANNALES UNIVERSITATIS APULENSIS - SERIES JURIPRDENTIA, 2012)
Among the fundamental and inalienable human rights is of course ius conubii. This is a personal right which translates in judicial terms the natural trend of man to marriage which may not be touched by a human law without affecting the human dignity. By this “right” the church has tried to be the oriflamme to provide and facilitate to each man the access to free marital life without any constraint from any authority meant to repress this freedom.  Keywords: human rights, ius conubii, marriage, to free marital life, human law, human dignity.